2013
DOI: 10.1111/cdoe.12089
|View full text |Cite
|
Sign up to set email alerts
|

The association between oral health literacy and failed appointments in adults attending a university‐based general dental clinic

Abstract: Objectives The purpose of this study is to determine the association between personal characteristics, a person’s oral health literacy, and failing to show for dental appointments at a university dental clinic. Methods A secondary data analysis was conducted on data collected from 200 adults at a university dental clinic between January, 2005 and December, 2006. In the original study, an oral health literacy instrument, the Rapid Estimate of Adult Literacy in Medicine and Dentistry (REALM-D), was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 36 publications
2
69
1
Order By: Relevance
“…According to the IOM, low OHL in the United States creates challenges in recognizing the risk for oral diseases as well as in seeking and receiving dental care (IOM 2011(IOM , 2013Holtzman et al 2014). Holtzman and colleagues (2014) found that adults who use fewer sources of oral health information, a subset of health literacy skills, were more likely to fail appointments at a university-based dental clinic.…”
Section: Introductionmentioning
confidence: 99%
“…According to the IOM, low OHL in the United States creates challenges in recognizing the risk for oral diseases as well as in seeking and receiving dental care (IOM 2011(IOM , 2013Holtzman et al 2014). Holtzman and colleagues (2014) found that adults who use fewer sources of oral health information, a subset of health literacy skills, were more likely to fail appointments at a university-based dental clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Oral HL (OHL) focuses specifically on the complexity of factors that affect the ability of an individual to make judgments and decisions concerning their oral health 7 . Lower OHL has been associated with: 1) less dental knowledge; 8–13 2) self‐report of poor oral health; 11,14‐17 3) irregular follow‐up dental visits; 14 4) less seeking of health information; 14 , 18 and 5) less access to dental care 10 , 12 , 18 . Some measures of periodontal disease (e.g., periodontal severity/attachment loss; decayed, missing, and filled teeth; missing teeth; and Lactobacillus levels) have also been shown to be associated with OHL 13 , 19 , 20 .…”
mentioning
confidence: 99%
“…Because high counts of lactobacillus in saliva reflect the consumption of simple carbohydrates by the host over time [43], we interpret our results that those with [18]. A study from Japan [44] found association between oral health literacy and clinical oral health such as DMFT and CPI.…”
Section: Discussionmentioning
confidence: 51%
“…A study from US found that increased oral health literacy is associated with better self-reported oral health status, and that self-efficacy may mediate the effect of oral health literacy on oral health status [17]. Other recent publications have demonstrated an association between oral health literacy levels and failing to show for dental appointments [18], and that low health literacy is associated with more severe periodontal disease [19].…”
Section: Introductionmentioning
confidence: 99%